2021
DOI: 10.1186/s13104-020-05428-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microRNA-223 and microRNA-125a expression association with STAT3 and Bcl2 genes in blood leukocytes of CLL patients: a case–control study

Abstract: Objective In chronic lymphocytic leukemia (CLL), lack of expression or dysregulation of some special miRs disrupts apoptosis of malignant cells; thereby miR expression can enhance cell proliferation, disease progression and decrease patient survival. Results 30 CLL patients and 20 healthy individuals participated in the study. RNA was extracted to evaluate the expression of miR-125, miR-223, BCL-2 and signal transducer and transcription 3 activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
5
0
3
Order By: Relevance
“…:10.31557/APJCP.2022.23.8.2735 miRNA 223/125a, COBLL1, andROR-1 Expression in B-chronic Lymphocytic Leukemia In our study, we reported that miRNA 223/125a expression was inversely correlated to WBC count and platelet count while it was directly correlated with hemoglobin (Hb) concentration. These findings agreed with Davari et al, (2021). They stated that these miRNAs may have regulatory effects by controlling WBC production based on the inverse correlation between WBC count and Hb concentration.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…:10.31557/APJCP.2022.23.8.2735 miRNA 223/125a, COBLL1, andROR-1 Expression in B-chronic Lymphocytic Leukemia In our study, we reported that miRNA 223/125a expression was inversely correlated to WBC count and platelet count while it was directly correlated with hemoglobin (Hb) concentration. These findings agreed with Davari et al, (2021). They stated that these miRNAs may have regulatory effects by controlling WBC production based on the inverse correlation between WBC count and Hb concentration.…”
Section: Discussionsupporting
confidence: 84%
“…miRNA 223 and miRNA 125a as tumor suppressor genes target multiple transcription factors like STAT3 (Chen et al, 2012;Fan et al, 2015). Davari et al (2021) found that miRNA-125a and miRNA-223 expression decreased in the patients with CLL compared to the control group. In addition, upregulation of their target genes, BCL-2 and STAT3, was observed in CLL compared to the control subjects.…”
Section: Research Articlementioning
confidence: 97%
See 1 more Smart Citation
“…Its usefulness is illustrated with the GAPDH phylogeny (Data set 5). Briefly, two different trees were built after enriching the same starting set of sequences from high-quality proteomes [ 19 ], one using all 570 samples from plastid-bearing organisms and the other using 172 transcriptomes resulting from our pipeline. The comparison of these two trees shows that the enrichment performed with the data set described here is less contaminated, less redundant and more balanced from a taxonomic point of view, thereby allowing more robust evolutionary interpretations.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The importance of miRNAs in CLL progno-According to the results of this study, hsa-miR-29a, hsa-miR-150-5p, and hsa-miR-155-5p were moderately predictive biomarkers for CLL risk, while no correlation between hsa-miR-16-5p and hsa-miR-223-3p levels and the risk of CLL was detected[131]. Recently, it was discovered that CLL patients have decreased levels of miR-223 and miR-125a, as well as greater levels of their targets BCL-2 and STAT3[132].…”
mentioning
confidence: 99%